RELATIONSHIP OF ONE SIDE CHEWING HABITS TO TEMPOROMANDIBULAR JOINT DISORDERS OCCURRENCE - Rheni Safira Isnaeni; Azkya Patria; Intan Renita Silvana (Journal of Health and Dental Sciences, 2022)
ABSTRACT The temporomandibular joint is called temporomandibular disorder (TMD) and it can be characterized by pain, limited mouth opening, masticatory disorders, joint sounds (clicking or tapping sound), crepitus, tinnitus, and persistent headache. The causes of temporomandibular joint disorders are multifactorial. The most common occurrences of these disorders are tooth loss, bad habits are bruxism, chewing on one side, and leaning on the chin. This study aimed to determine the relationship between one-sided chewing habits and the incidence of temporomandibular joint disorders in students of the Faculty of Medicine and Faculty of Dentistry, batch 2020. This research was an analytic study with a cross-sectional approach. The data were analyzed using the chi-square test with 245 research subjects from the Faculty of Medicine and the Faculty of Dentistry, batch 2020. This study used a questionnaire in the form of a g-form which was adapted from the AAOP questionnaire and distributed to all students of Jenderal Achmad Yani University Batch 2020. The results of this study found that 168 students (88.89%) have the habit of chewing on one side and the symptoms of temporomandibular joint disorders with a value of p = 0.021. It can be concluded that in this study, there is a relationship between one-sided chewing habits and symptoms of temporomandibular joint disorders. DOI : 10.54052/jhds.v2n2.p279-302